A marginal Jew : rethinking the historical Jesus - Meier, John P. (New York : Doubleday, 1991)
Contents: v. 1 Origins of the problem and the person. v.2 Mentor, message, and miracles .
Includes bibliographical references and index
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Jewishness